Study of Hyponatremia in Acute CNS Infections in A Tertiary Center - Bhattarai, Prabin; Karn, Ragesh; Ojha , Rajeev (Journal of Advances in Internal Medicine, 2024)
INTRODUCTION Hyponatremia significantly contributes to morbidity and mortality in CNS infections. Accurate diagnosis and timely intervention of hyponatremia is necessary as it can exacerbate the symptoms and may cause delay in management. METHODS This cross-sectional study was done in 146 consenting adults diagnosed with acute CNS infections at Tribhuvan University Teaching Hospital (TUTH) over one year. All participants underwent clinical assessments, including cerebrospinal fluid (CSF) analysis, blood tests, and imaging. Prevalence and severity of hyponatremia was studied. Data was entered into MS Excel and subsequently transformed into IBM SPSS Software version 25 for statistical assessment. RESULTS Hyponatremia was prevalent in 34.25% of cases; of which 56% were moderate in severity. Altered mental state, fever, and headache were common clinical features. In terms of etiology, viral infections (45.8%), followed by CNS TB (30.8%) were common. CONCLUSION Our study identified that hyponatremia was prevalent in more than one third of patients having CNS infections, encephalitis being the most common clinical syndrome. In terms of etiology, viral infections constituted the majority, followed by tubercular, bacterial, fungal, and parasitic infections.